2014
DOI: 10.3109/13697137.2014.966241
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of phytoestrogens for menopausal symptoms: a meta-analysis and systematic review

Abstract: ObjectiveTo perform a meta-analysis examining the efficacy of phytoestrogens for the relief of menopausal symptoms.MethodsMedline, Cochrane, EMBASE, and Google Scholar databases were searched until September 30, 2013 using the following key words: vasomotor symptoms, menopausal symptoms, phytoestrogens, isoflavones, coumestrol, soy, red clover. Inclusion criteria were (1) randomized controlled trial (RCT), (2) perimenopausal or postmenopausal women experiencing menopausal symptoms, (3) intervention with an ora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
132
0
24

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 249 publications
(160 citation statements)
references
References 42 publications
4
132
0
24
Order By: Relevance
“…Therefore reduction in these symptoms inturn reduces the severity of mood distress. 28 Some studies have shown that red clover has no effect on vasomotor and psychological symptoms 29,30 . There are differences among the results of these individual studies; moreover, systemic and meta-analyses have provided contradictory results 12,29-32 .…”
Section: Sleep Disturbance Followed By Vasomotor Symptoms Can Negativmentioning
confidence: 99%
“…Therefore reduction in these symptoms inturn reduces the severity of mood distress. 28 Some studies have shown that red clover has no effect on vasomotor and psychological symptoms 29,30 . There are differences among the results of these individual studies; moreover, systemic and meta-analyses have provided contradictory results 12,29-32 .…”
Section: Sleep Disturbance Followed By Vasomotor Symptoms Can Negativmentioning
confidence: 99%
“…Chen et al [9] publizierten kürzlich eine Meta-Analyse über die Wirksamkeit von Isoflavon-haltigen Präparaten bei menopausalen Beschwerden und werteten 9 randomisierte kontrollierte Studien (RCT) aus. Bei 7 Studien wurde zur Wirksamkeitsbestimmung der Kupperman-Index verwendet.…”
Section: Isoflavoneunclassified
“…Drawing on a similar pool of research material, Chen and colleagues 19 found 15 RCTs that met criteria for use in a meta-analysis. The mean daily hot flush frequency was statistically lower in the isoflavone study groups (reduction mean 5 0.89, CI 0.2-1.52, P<.005).…”
Section: Alternative Approaches To Menopausementioning
confidence: 99%